AB0882 BMD and TBS use in Adult Patients Suffering Polio. (9th June 2015) - Grados, D.; Di Gregorio, S.; Pasarin, A.; Allue, N.; Bonel, E.; García, M.; Winzenrieth, R.; del Rio, L.; Erra, A.
Abstract : Objectives: Assess TBS to categorize skeletal status in adult subject which history of Poliomyelitis sequels in limbs. Methods: We scan total body, lumbar spine (L1-L4) and both hips (Total femur and Femoral Neck ROI's) in 58 patients with history of poliomyelitis infection and limb paralysis (men: 14 -57.5 years; women: 48 -57±8.5 years). A DXA device GE-iDXA model was used. The difference between affected extremity and the opposite in BMD T-score and trabecular microarchitecture assessed by TBS (TBS® Insight; Medimaps) were used. The results were stratified as normal, low bone density or osteoporosis taking the lower T-score of the scanned regions of interest. TBS results were categorized as normal (TBS N) ≥1.350; partially deteriorated-(TBS-PD) between: 1.250 -1.349, and significantly deteriorated (TBS-SD): <1.250. Results: Three patients had hip fracture history. The left limb was the extremity most affected in this group (32 vs 20). Five patients had both extremities affected, with more severe affectation on the right side (4/5). Only 7 patients had normal BMD of the hip, which contrasts with the 43.1% of patients with normal lumbar BMD. The TBS was normal in 16 patients (27.6%). Stratification was more similar in patients who had a low bone density (48.3% in the hip and 50% in lumbar spine) and TBS-PD (50%). In patients categorized as osteoporotic the lowest T-score of BMD was found in proximal femur (39.7%) of the most affected limb, the T-score BMD of the lumbar spine in 6.9% of the patients, while the TBS-SD was found at 22.4%. The DXA spine images showed a spondyloarthritis and scoliosis signs in 25 patients. 16.7% of patients had a osteoporotic T-score in affected femur and had normal BMD at the lumbar spine and opposite femur, but interestingly had a deteriorated TBS (TBS-PPD and TB SSD). Conclusions: A degradation TBS allow identify a greater number of patients who had polio with low bone status than assess BMD of lumbar spine and femur. Postural instability could increase irregular mechanical charges to lumbar spine and femur unaffected that may decrease the sensitivity of DXA when only the BMD is used to classify patients. Disclosure of Interest: None declared